Synthesis of Calcium Silicate Hydrate Compounds From Wet Flue Gas Desulfurization (FGD) Waste - Denise Alves Fungaro; Lucas Caetano Grosche; Juliana de Carvalho Izidoro (AMTS and Faculty of Engineering - Universitas Riau, 2020)
In this study Calcium silicate hydrate based products (CSHP) were synthesized from wet flue gas desulfurization waste (FGD) by alkali fusion followed by hydrothermal treatment. The effect of various factors on the formation of products, such as mineralizing agent, fusion temperature and time, crystallization time and addition of Ca and Si were studied as well as the conditions optimized. The FGD and synthesized materials were characterized by using X-Ray (XRD), Scanning Electron Microscope (SEM), X-ray fluorescence (XFR), among other methods. A fusion temperature of 600 °C with NaOH, fusion duration of 1 h, and a subsequent hydrothermal temperature of 100 °C for a reaction of 24 h were found to be the optimal conditions. In these synthesis conditions, CSHP containing tobermorite and Al-tobermorite was the major phases. The synthesized CSHP revealed high selective uptake for Cs+ in water. The maximum adsorption capacity of Cs+ onto the synthesized material, as calculated from the Langmuir model, was 1949 µmol g-1. The performance on the Cs+ removal in the presence of high Na+ contents was also evaluated. The adsorbent material showed a high Cs+ adsorption capacity in deionized water and a decrease of 56% and 62% in saturated media with the Na+ ions and seawater, respectively. Therefore, CSHP as a higher value-added product can be obtained from a by-product of a coal-fired power plant, which has wide range applications, including for Cs+ removal from wastewater.